2021
DOI: 10.3389/fnmol.2021.720973
|View full text |Cite
|
Sign up to set email alerts
|

PRDM12 Is Transcriptionally Active and Required for Nociceptor Function Throughout Life

Abstract: PR domain-containing member 12 (PRDM12) is a key developmental transcription factor in sensory neuronal specification and survival. Patients with rare deleterious variants in PRDM12 are born with congenital insensitivity to pain (CIP) due to the complete absence of a subtype of peripheral neurons that detect pain. In this paper, we report two additional CIP cases with a novel homozygous PRDM12 variant. To elucidate the function of PRDM12 during mammalian development and adulthood, we generated temporal and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…We originally observed a significant change in expression of MEOX2 mRNA in fibroblasts harvested from CIP patients with mutations in a methyl transferase, PRDM12 [8]. While we found co‐labelling of PRDM12 and MEOX2 in a small number of cells in the adult mouse DRG (not shown), we did not detect dysregulated Meox2 mRNA levels in classical PRDM12 knock‐out mice [63] nor in specific PRDM12 DRG‐specific knock outs ( Prdm12fl/fl; Avil‐Cre + ) by RNAseq [64]. Likewise, we were also unable to detect any changes in MEOX2 protein levels in Prdm12fl/fl; Avil‐Cre + DRG by Western blotting (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…We originally observed a significant change in expression of MEOX2 mRNA in fibroblasts harvested from CIP patients with mutations in a methyl transferase, PRDM12 [8]. While we found co‐labelling of PRDM12 and MEOX2 in a small number of cells in the adult mouse DRG (not shown), we did not detect dysregulated Meox2 mRNA levels in classical PRDM12 knock‐out mice [63] nor in specific PRDM12 DRG‐specific knock outs ( Prdm12fl/fl; Avil‐Cre + ) by RNAseq [64]. Likewise, we were also unable to detect any changes in MEOX2 protein levels in Prdm12fl/fl; Avil‐Cre + DRG by Western blotting (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…PRDM12 function was subsequently assayed in mammalian model systems. While germline deletion of PRDM12 and conditional knockout of PRDM12 in the embryonic neural crest was neonatal lethal, conditional knockout of PRDM12 in embryonic DRGs produced viable offspring (Kokotović et al, 2021 ; Landy et al, 2021 ). These mice displayed increased mortality and exhibited corneal abrasions and facial scarring similar to what is seen in human CIP patients; they also displayed decreased baseline sensitivity to mechanical and cold stimulation, decreased chemical sensitivity to capsaicin injection, and decreased itch response to chloroquine and histamine.…”
Section: Resultsmentioning
confidence: 99%
“…Although this article was under revision, Kokotovic and colleagues also reported that Prdm12 is required for nociceptor function in adult mice. 5,28 Further studies are obviously needed to better understand the complex mechanisms by which Prdm12 controls nociceptive neuron properties.…”
Section: Discussionmentioning
confidence: 99%